2014
DOI: 10.1071/sb14043
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the fern family Aspleniaceae in Australasia and the south-western Pacific

Abstract: Abstract. Aspleniaceae is one of the largest fern families. It is species-rich in Australasia and the south-western Pacific (ASWP), where approximately 115 species occur. In the current study, the chloroplast regions rbcL, trnL-trnF and rps4-trnS were sequenced for 100 Aspleniaceae samples from ASWP. These data were combined with published sequences for species from New Zealand and other regions for phylogenetic analyses. Species of Aspleniaceae from ASWP were placed in six of the eight previously identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 57 publications
1
15
1
Order By: Relevance
“…Asplenium is somewhat unusual in having large numbers of both epiphytic and terrestrial species, and for having had major radiations in both tropical and north‐temperate areas. Many species of the genus often occur in the forest floor, on banks of rivers, and in ravines in montane vegetation, and islands often harbour endemic species (Ohlsen et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asplenium is somewhat unusual in having large numbers of both epiphytic and terrestrial species, and for having had major radiations in both tropical and north‐temperate areas. Many species of the genus often occur in the forest floor, on banks of rivers, and in ravines in montane vegetation, and islands often harbour endemic species (Ohlsen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…(Murakami, ; Murakami et al., 1998, 1999a; Pinter et al., ; van den Heede et al., ; Schneider et al., , , ; Perrie and Brownsey, ; Schuettpelz and Pryer, ; Bellefroid et al., ; Dong et al. 2012; Rothfels et al., ,b; Ohlsen et al., ; Lóriga et al., ; Sessa et al., ; Xu et al., ). Anatomical studies have shown that the stelar structure of the rhizomes in Asplenium is dictyostelic or radial, whereas that of Hymenasplenium is dorsiventral (Hayata, ; Bir, ; Iwatsuki and Kato, ; Smith, ; Mitsuta et al., ; Kato et al., ; Murakami, ; Umikalsom, ; Bercu, ; Gabancho and Prada, ; Nopun et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Material and Methods 2.1 Reconstructing the phylogenetic framework A phylogeny was reconstructed by taking advantage of a large range of studies focusing either on the global phylogeny of Aspleniaceae (Murakami et al, 1999;Schneider et al, 2004Schneider et al, , 2005Leroux et al, 2011) or particular species and species complexes (e.g., Murakami, 1995;Schulze et al, 2001;Pinter et al, 2002;Perrie & Brownsey, 2005;Li & Lu, 2006;Shepherd et al, 2008aShepherd et al, , 2008bBellefroid et al, 2010;Perrie et al, 2010;Dyer et al, 2012Dyer et al, , 2013Schneider et al, 2012;Chang et al, 2013;Ohlsen et al, 2014;Loriga et al, 2017). The majority of these studies used the DNA sequences of rbcL, the chloroplast coded large subunit of the RUBISCO enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…distribution patterns in Scleranthus Linnaeus (1753a: 406; also in New Zealand, Smissen et al 2003), Austrobryonia Schaefer in Schaefer et al (2008: 126), Bryonia Linnaeus (1753bLinnaeus ( : 1012, Ecballium Richard in De Saint-Vincent (1824: 19) (Schaefer et al 2008), and Pleurosorus Fee (1852: 179, t. 16.C; also in New Zealand and South America, Ohlsen et al 2015). Australia-Asia floristic relationships tend to be between Southeast Asia and northern Australia in tropical groups.…”
Section: Discussionmentioning
confidence: 97%